Analisis produksi telur peternakan ayam petelur di Kabupaten Kuningan Provinsi Jawa Barat - Atmadji, Eko; Hafidhin, Fahmi (Jurnal Kebijakan Ekonomi dan Keuangan, 2024)
Purpose – This study analyze production of laying hen farms in Kuningan Regency using Cobb Douglas model and non-linear methods. Methods – This study applies cluster method to select samples after determining the number of samples. The analysis method uses the Cobb Douglas production function. The Cobb Douglas model estimation employs a non-linear method, the Marquardt method. The production function model is that the amount of egg production is influenced by company capital and farm workers, whereas the estimation results are in the form of production elasticity numbers for capital and production elasticity numbers for workers. From the results of the estimated coefficients from the Cobb Douglas equation, this study obtains the category of returns to scale from laying hen farms in Kuningan Regency. Findings – The findings of this study indicate that Non-Performing Loans (NPL) and Bank Operating Expenses to Operating Income (BOPO) have quite a large negative impact, but the Loan to Deposit Ratio (LDR) has a large beneficial impact on the Bank's Return on Assets (ROA) and Return on Equity (ROE). Implication – The employment of capital is under capacity and the use of workers is over capacity. It means that breeders have to start utilizing their capital more, therefore egg production is more efficient. Originality – This study employs Cobb Douglas production function model with non-linear estimation. Abstrak Tujuan – Penelitian ini menganalisis produksi di peternakan ayam petelur Kabupaten Kuningan dengan menggunakan model Cobb Douglas dan metode non linier. Metode – Penelitian ini menggunakan metode kluster untuk memilih sampel setelah ditentukan jumlah sampelnya. Metode analisis menggunakan fungsi produksi Cobb Douglas. Estimasi model Cobb Douglas menggunakan metode non linier yaitu metode marquardt. Model fungsi produksinya adalah jumlah produksi telur dipengaruhi oleh kapital perusahaan dan pekerja peternakan dimana hasil estimasinya berupa angka elastisitas produksi atas kapital dan angka elastistisitas produksi atas pekerja. Dari hasil estimasi koefisien dari persamaan Cobb Douglas didapat jenis returns to scale dari peternakan ayam petelur di Kabupaten Kuningan. Temuan – Berdasarkan hasil estimasi, penggunaan kapital masih berada di tahap 1 kurva produksi, sedangkan penggunaan pekerja berada di tahap 3. Secara total skala produksinya adalah increasing returns to scale. Implikasi – Adanya penggunaan kapital yang di bawah kapasitas dan penggunaan pekerja di atas kapasitas, menyebabkan para peternak harus mulai lebih mendayagunakan kapitalnya agar produksi telur makin efisien. Orisinalitas – Studi ini menggunakan model fungsi produksi Cobb Douglas dengan estimasi non linier.